Penegakan Hukum Terhadap Peredaran Narkotika Jenis New Psychoactive Subtance di Indonesia - Lisa Lisa; Deassy Jacomina Anthoneta Hehanussa; Yonna Beatrix Salamor (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: NPS or new psychoactive substance is a new type of narcotic where the type of substance or content contained in it has not been regulated or has not been classified in legal regulations in Indonesia.Purposes of the Research: To analyze and discuss formulation policies against NPS narcotics. Reviewing and discussing the obstacles encountered in law enforcement against the circulation of NPS narcotics in Indonesia. As one of the requirements to obtain a Bachelor of Laws degree at the Faculty of Law, University of Pattimura. Methods of the Research: This research is a normative juridical research. In this study, three approaches to the problem are used, namely the statutory approach and the conceptual approach and the case approach. Sources of data obtained are primary legal materials, and secondary legal materials. The technique of collecting legal materials is by collecting and grouping them according to their respective parts, both primary and secondary law. All data in this study were analyzed qualitatively.Results of the Research: The results of this study indicate that from several alternative formulation policies of the Narcotics Law, the appropriate formulation policy to be applied in the future is to change the provisions of Article 6 of the Narcotics Law as follows: narcotics as referred to in Article 5: narcotics class I, narcotics class I II, class III narcotics, all derivatives of class I, II, III narcotics. Although in the future, all evidence must be presented by experts in court to determine whether a particular class of substance is included in the definition of narcotics in the Narcotics Act. But we must prevent all new types of narcotic crimes from escaping the law while maintaining legal certainty. Meanwhile, law enforcement against the circulation of NPS narcotics in Indonesia has not been going well. This is because there are still obstacles encountered in law enforcement against the circulation of NPS narcotics in Indonesia, namely: legal substance factors, law enforcement factors, facilities and infrastructure factors, modes that are always changing and the silent movement carried out by suspects and factors geographical conditions of the Unitary State of the Republic of Indonesia (NKRI).